2019
DOI: 10.3390/ijms20184372
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity Phosphatases: From Molecular Mechanisms to Biological Function

Abstract: Dual specificity phosphatases (DUSPs) constitute a heterogeneous group of enzymes, relevant in human disease, which belong to the class I Cys-based group of protein tyrosine phosphatase (PTP) gene superfamily [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…On the other hand, dephosphorylation of MAPKs is one of the most efficient mechanisms to control their activation. Dual specificity phosphatases (DUSP), also termed MKP can negatively regulate MAPKs activation through dephosphorylation of phosphotyrosine and phosphothreonine residues ( 24 ). DUSPs can be induced by TLR-mediated activation of MAPKs, creating a negative feedback loop to limit MAPKs activation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dephosphorylation of MAPKs is one of the most efficient mechanisms to control their activation. Dual specificity phosphatases (DUSP), also termed MKP can negatively regulate MAPKs activation through dephosphorylation of phosphotyrosine and phosphothreonine residues ( 24 ). DUSPs can be induced by TLR-mediated activation of MAPKs, creating a negative feedback loop to limit MAPKs activation.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies have indicated that Mitogen-activated protein kinase (MAPK) pathways, including extracellular signal-regulated kinase 1/2 (ERK1/2), p38 mitogen-activated protein kinase and c-Jun NH2-terminal kinase (JNK), are involved in the inflammatory response and development of airway remodeling during childhood asthma ( Lee et al, 2019b ; Jia et al, 2019 ). Concretely, ERK1/2 is involved in airway remodeling ( Defnet et al, 2019 ), while p38 MAPK and JNK are considered as anti-inflammation targets to regulate inflammatory processes via phosphorylation of downstream mediators in childhood asthma ( Kim and Choi, 2010 ; Pulido and Lang, 2019 ; Theodorou et al, 2022 ). However, literatures about the pathogenesis of MAPK pathways in childhood asthma are limited.…”
Section: Asthma-associated Pathogenesismentioning
confidence: 99%
“…Besides, dual-specificity phosphatase 6 (DUSP6) was reported to sponge miR-145-5p and thus further implicated in the regulation of chronic obstructive pulmonary disease [12]. DUSP, as a heterogeneous cluster of enzymes of the protein tyrosine phosphatase gene superfamily, is differentially expressed in resting and activated immune cells [13,14]. More importantly, DUSP6 was identified as a crucial player in the intervention of inflammatory bowel disease [15].…”
Section: Introductionmentioning
confidence: 99%